Hidup Damai Berdasarkan Pesan- Pesan Yohanes Paulus II pada Hari Perdamaian Dunia Tahun 2002-2005 - Mulyatno, CB. (Jurnal Orientasi Baru, 2014)
John Paul II is well-known as an enduring voice of peace for the world. What is the meaning of peace according to John Paul II? The focus of this research is to find the thought of John Paul II on peace. It employs a reflective method for analyzing the massages of John Paul II for the celebration of the world day of peace from 2002 to 2005. He expressed that the pillars of peace are justice, freedom, forgiveness, love, solidarity and common good. Peace should be born in the heart of each person. Peace shall grow in a coexistence of life of mutual respect. Respect on human rights and dignity is a fundamental moral law for developing peace in the world. Responsibility to develop a peaceful world in the context of continuous conflicts and wars in our world belongs to each person and all institutions. Each person as well as community are called to work for common good that is a social face of peace.